2y+3=3(2)-7

Simple and best practice solution for 2y+3=3(2)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+3=3(2)-7 equation:


Simplifying
2y + 3 = 3(2) + -7

Reorder the terms:
3 + 2y = 3(2) + -7

Multiply 3 * 2
3 + 2y = 6 + -7

Combine like terms: 6 + -7 = -1
3 + 2y = -1

Solving
3 + 2y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2y = -1 + -3

Combine like terms: 3 + -3 = 0
0 + 2y = -1 + -3
2y = -1 + -3

Combine like terms: -1 + -3 = -4
2y = -4

Divide each side by '2'.
y = -2

Simplifying
y = -2

See similar equations:

| 6x-10=158 | | n+6=8*7 | | (0.35)(s+0.34)+(0.15s)=(0.2s-1.66) | | 9(b+1)=3b+15 | | 3g+2(-7+3g)=1-g | | (3x+5y)-(4x+11)=0 | | 17y-5x=46 | | .14(14+3.5)-3q=9 | | -5=r-13 | | 2y+3=3(-2)-7 | | x-1(4x-7)=5x-(x+21) | | 3(x-9)=-39-x | | 7x+3=-7.5 | | (-A-5B+2)5AB= | | -4+6x=-34 | | 0.3(r+2)=-1.0(-2r-4) | | 6t^2+2t=2t(3t+1) | | 2y+3=3(0)-7 | | -7(p-8)= | | -2v-14=8(v+2) | | 4t=38+2t | | n-8=22+4 | | 3(4+4n)=18n+12-6n | | -5(x+7)= | | (2x+4)x=240 | | 6/15=3/x | | 2n^2=90 | | x(6)=60 | | n+3=17+4 | | 9h+11=5h-17 | | 2x(2x)= | | x(13)=52 |

Equations solver categories